2021
DOI: 10.1021/acs.macromol.1c00461
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Polyketone via Chlorodimethylsilane-Mediated Reductive Etherification Reaction: A Practical Way for Alkoxy-Functional Polymers

Abstract: This study describes a straightforward post-polymerization modification (PPM) methodology from polyketone via chlorodimethylsilane (CDMS)-mediated reductive etherification reaction (RER). The polyketone platform was prepared via acyclic diene metathesis (ADMET) polymerization and reacted with a variety of alcohols in the presence of CDMS to create a wide range of polymers possessing pendant functional-alkoxy structures under mild conditions. The effect of parameters such as solvents and the amount of reactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…As highlighted in the introduction part, the formation of alcohol segment due to reduction of the carbonyl to alcohol was inevitable during the functionalization of polyketone via CDMS-mediated RERs . Given this information, we hypothesized that if such a reduction occurs, this may lead to a loss at the aldehyde end, which in turn may trigger the self-condensation polymerization of TPA.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…As highlighted in the introduction part, the formation of alcohol segment due to reduction of the carbonyl to alcohol was inevitable during the functionalization of polyketone via CDMS-mediated RERs . Given this information, we hypothesized that if such a reduction occurs, this may lead to a loss at the aldehyde end, which in turn may trigger the self-condensation polymerization of TPA.…”
Section: Resultsmentioning
confidence: 97%
“…First, the equivalent optimization study for TPA, BD, and CDMS was performed, and the results are summarized in Table . We previously reported that CH 3 NO 2 was an essential solvent for CDMS-mediated RER, and excess amounts of CDMS were required for high RER efficiency . Hence, in the first attempt equimolar amounts of TPA and BD were reacted in 1 mL of CH 3 NO 2 using 4 equiv of CDMS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations